Ontology, Conceptualization and Epistemology for Information Systems, Software Engineering and Service Science 4th International Workshop, ONTOSE 2010, held at CAiSE 2010, Hammamet, Tunisia, June 7-8, 2010, Revised Selected Papers - Sicilia, Miguel-Angel.; Kop, Christian; Sartori, Fabio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the post-conference proceedings of the International Workshop on Ontology, Conceptualization and Epistemology for Information Systems, Software Engineering and Service Sciences (ONTOSE 2010), held at the CAiSE 2010 conference in Hammamet, Tunisia, June, 2010. The 10 papers presented in this volume were carefully revised and selected from 25 submissions. They are grouped in sections on enterprise and service architectures, ontology applications, ontology visualization and query expansion, and ontologies for services.
Enterprise and Service Architectures -- Identification and Specification of Relationships as the Foundation for Service Bundling -- Conceptual Modeling and Integration of Static and Dynamic Aspects of Service Architectures -- Exemplifying a Framework for Interrelating Enterprise Architecture Concerns -- Ontology Applications -- Ontology Representations for Information Exchange between Communities -- A Specification-Oriented Geospatial Coverage Ontology Study -- A Space-Based Interoperability Model -- Ontology Visualization and Query Expansion -- Visualising Semantic Coupling among Entities in an OWL Ontology -- Query Expansion for the Legal Domain: A Case Study from the JUMAS Project -- Ontology for Services -- A Mereology-Based Ontology for Services Science: Example of an e-health Service Modelling -- On Using the REA Enterprise Ontology as a Foundation for Service System Representations.
Keywords: Economics; Information systems; Artificial intelligence; Management information systems; Economics/Management Science; Business Information Systems; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).